The Effect of Compensation and Supervisor Support Mediated by Job Satisfaction on Employee Retention (Case Study at PT Pradu) - Hery Winoto Tj; Melitina Tecualu; Shierli Wijaya (Fakultas Bisnis, 2021)
The purpose of this study is to analyze whether the compensation and supervisor support variables mediated by job satisfaction affect employee retention at PT Pradu. The population in this study were 55 employees of the non-academic division. The sampling technique used in this study was total sampling, namely the sampling technique where the number was the same as the population. The type of data used in this study uses primary data which is done by distributing questionnaires directly to Pradu employees. The research data analysis technique used structural equation modeling (SEM) with the Smart PLS (Partial Least Square) version 3.2.7 program. The results of data analysis found that the R-square of the compensation and supervisor support variables in explaining the job satisfaction variable was 0.701 or about 70% and 30% was explained by other factors outside of this study. While the compensation variable, supervisor support, and job satisfaction in explaining the employee retention variable amounted to 0.325 or about 32.5% and 67.5% was explained by other factors outside of this study. A total of 5 hypotheses were accepted and 2 hypotheses were rejected after testing with the limit of t-statistics> t-table 1.96 and P-Value ​